CLINICAL STUDY ON EFFICACY OF PANCHAJEERAKA GUDA IN SUTIKA PARICHARYA - Wahi Meenu; Attri Vishavender (International Journal of Applied Ayurved Research, 2016)
Women get exhausted by labor pains and constant bearing down efforts. If proper daily regimen is not followed, she becomes prone to many diseases that become difficult to treat or incurable. Therefore, the present study was carried out to evaluate the role of Panchjeeraka guda in sutika paricharya. The treatment was conducted for duration of 45 days and response to the treatment was recorded by parameters , the result revealed that this ayurvedic drug is very beneficial for easy recovery in sutika